Health Care Utilization and Costs in Patients With Migraine Who Have Failed Previous Preventive Treatments. Issue 3 (June 2021) - Newman, Lawrence; Vo, Pamela; Zhou, Lujia; Lopez Lopez, Cristina; Cheadle, Andy; Olson, Melvin; Fang, Juanzhi
Abstract : Objective: To characterize health care utilization (HCU) and associated costs among patients with migraine categorized by the number of preventive treatment failures (TFs; 1 TF, 2 TFs, and 3+ TFs) using real-world data. Methods: This retrospective analysis identified adults with incident migraine diagnosis in the IBM MarketScan Commercial and Medicare Supplemental database between January 1, 2011, and June 30, 2015. TF was defined in the 2 years after the first migraine diagnosis period. One TF, 2 TFs, and 3+ TFs were defined as patients who had received only 2 preventive treatments (PTs), 3 PTs, and 4+ PTs in the 2-year period, respectively. A negative binomial model was used to analyze HCU data, and a 2-part model was used for cost data controlling for the preindex Deyo-Charlson Comorbidity Index. Results: Overall, 24, 282 patients with incident migraine who had failed at least 1 PT were included in the analysis. Of these, 72.7% (n = 17, 653) had 1 TF, 20.2% (n = 4, 900) had 2 TFs, and 7.1% (n = 1, 729) had 3+ TFs. Adjusted annualized rates of all-cause and migraine-specific HCU increased with an increase in the number of TFs (1.4–4 times higher; all p < 0.0001 vs 1 TF). The mean total all-cause health care costs were higher by $3, 732 (95% confidence interval [CI]: $2, 708–$4, 588) in patients with 2 TFs and by $8, 912 (95% CI: $7, 141–$10, 822) in patients with 3+ TFs vs those with 1 TF. Outpatient costs were the key drivers of differences in health care costs. Conclusions: TF in patients with migraine was associated with a substantial resource and cost burden, which increased with the number of TFs.